Hybrid reconstruction of bronchial dehiscence following lung transplant. Issue 11 (28th September 2020) - Ram, Duvuru; O′Carroll, Mark; Sibal, Amul Kumar
Abstract: Surgical repair of right‐sided bronchial dehiscence post lung transplant is challenging. We report a hybrid reconstruction of the bronchus using an aortic homograft patch with stenting as a novel technique of management of ischemic airway injury following lung transplantation.